Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.tsf.2011.01.382
|View full text |Cite
|
Sign up to set email alerts
|

Cr2O3 thin films grown at room temperature by low pressure laser chemical vapour deposition

Abstract: Chromia (Cr2O3) has been extensively explored for the purpose of developing widespread industrial applications, owing to the convergence of a variety of mechanical, physical and chemical properties in one single oxide material. Various methods have been used for large area synthesis of Cr2O3 films. However, for selective area growth and growth on thermally sensitive materials, laser-assisted chemical vapour deposition (LCVD) can be applied advantageously.Here we report on the growth of single layers of pure Cr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Cr 2 O 3 can be synthesized by many different techniques such as solution combustion [6], arc ion plating [7], pulsed laser deposition [8], plasma spraying [9], electrochemical deposition, magnetron sputtering, reactive sputtering [10][11][12], electron beam evaporation, spray pyrolysis, ion implantation and chemical vapor deposition (CVD) [13][14][15][16][17][18][19][20]. In recent years, a new method named pulsed-spray evaporation CVD (PSE-CVD) was used to synthesize pure transition metal oxides such as Co 3 O 4 and Mn 3 O 4 [21].…”
Section: Introductionmentioning
confidence: 99%
“…Cr 2 O 3 can be synthesized by many different techniques such as solution combustion [6], arc ion plating [7], pulsed laser deposition [8], plasma spraying [9], electrochemical deposition, magnetron sputtering, reactive sputtering [10][11][12], electron beam evaporation, spray pyrolysis, ion implantation and chemical vapor deposition (CVD) [13][14][15][16][17][18][19][20]. In recent years, a new method named pulsed-spray evaporation CVD (PSE-CVD) was used to synthesize pure transition metal oxides such as Co 3 O 4 and Mn 3 O 4 [21].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Cr 2 O 3 has been widely used in magnetic recording heads [3], bearings [4], and casing walls. Researchers deposited Cr 2 O 3 thin films using different techniques, such as plasma-spray [5], pulsed laser deposition [6], laser chemical vapor deposition [7], electrochemical deposition [8], direct current sputtering [9], reactive radio frequency magnetron sputtering [10], and arc ion plating (AIP) [11]. These studies mainly focused on the roles of deposition parameters and thermal treatment on the microstructure, mechanical properties, and tribological properties of Cr 2 O 3 films.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that chromium (III) oxide (Cr 2 O 3 ) coating was widely used in various fields, such as wear resistance, corrosion protection, electronics, and optics due to its very desirable properties such as mechanical strength, high hardness, chemical inertness, optical characteristics, and low friction coefficient …”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that chromium (III) oxide (Cr 2 O 3 ) coating was widely used in various fields, such as wear resistance, corrosion protection, electronics, and optics due to its very desirable properties such as mechanical strength, high hardness, chemical inertness, optical characteristics, and low friction coefficient. [1][2][3][4][5][6][7][8][9][10] In previous work, we have shown that Cr 2 O 3 coating could be easily electrophoretic deposited from suspension of acetylacetone and ethanol, and the electrophoretic Cr 2 O 3 coating could become uniform and dense after sintering treatment. 11 However, an aqueous electrophoretic deposition (EPD) has the advantages of lower deposition voltage, lower cost, and more attractively, a lower environmental protection cost.…”
Section: Introductionmentioning
confidence: 99%